IMPROVING READING SKILLS THROUGH AUTHENTIC MATERIALS (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
Learning reading skills through authentic materials is the best way for  learners because authentic materials provide real- life examples of language used in everyday situations. This will stimulate pleasure reading since students feel they are not reading simply for a final grade. Thus, they would in their native language. Authentic materials refer to resources that are created for real-world communication and are not specifically designed for language learning purposes. These materials can include newspapers, magazines, advertisements, videos, podcasts, social media posts.